A flexible dual-mode pressure sensor with ultra-high sensitivity based on BTO@MWCNTs core-shell nanofibers. (16th June 2022) - Zhou, Bangze; Li, Chenchen; Zhou, Yanfen; Liu, Zhanxu; Gao, Xue; Wang, Xueqin; Jiang, Liang; Tian, Mingwei; Zhou, Feng-Lei; Jerrams, Stephen; Yu, Jianyong
Abstract: Wearable flexible sensors have developed rapidly in recent years because of their improved capacity to detect human motion in wide-ranging situations. In order to meet the requirements of flexibility and low detection limits, a new pressure sensor was fabricated based on electrospun barium titanate/multi-wall carbon nanotubes (BTO@MWCNTs) core-shell nanofibers coated with styrene-ethylene-butene-styrene block copolymer (SEBS). The sensor material (BTO@MWCNTs/SEBS) had a SEBS to BTO/MWCNTs mass ratio of 20:1 and exhibited an excellent piezoelectricity over a wide range of workable pressures from 1 to 50 kPa, higher output current of 56.37 nA and a superior piezoresistivity over a broad working range of 20–110 kPa in compression. The sensor also exhibited good durability and repeatability under different pressures and under long-term cyclic loading. These properties make the composite ideal for applications requiring monitoring subtle pressure changes (exhalation, pulse rate) and finger movements. The pressure sensor developed based on BTO@MWCNTs core-shell nanofibers has demonstrated great potential to be assembled into intelligent wearable devices. Graphical abstract: Image 1 Highlights: A new pressure sensor was fabricated based on electrospun BTO@MWCNTs core-shell nanofibers and SEBS. The pressure sensor exhibited a working pressure range of 1–50 kPa and an output currentof 56.97 nA. The pressure sensor was capable of sensing in an ultra-wide working range (1–110 kPa).